EVALUATION OF CYTOTOXICITY AND APOPTOTIC POTENTIAL OF OPHIORRHIZA PECTINATA ARN. – A POTENT ANTICANCER AGENT - PREETHA MOL SN; JOHN E THOPPIL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Ophiorrhiza pectinata Arn., a notable species belonging to the family Rubiaceae, is reported to be used in traditional and conventional medicines. The present study was aimed at the evaluation of the cytotoxic and apoptotic effects of the aqueous extract of O. pectinata. Methods: Cytotoxic potential of the plant extract was analyzed using Allium cepa assay and the apoptotic effect of the plant extract was analyzed using Evan’s blue staining technique. Results: The extract was found to be cytotoxic at all tested concentrations, inducing several clastogenic and non-clastogenic aberrations at all the stages of mitosis. The clastogenic aberrations observed include chromosome coagulation, stickiness, chromosome bridges and fragments, nuclear lesions, and giant cells. Among non-clastogenic aberrations seen, the prominent ones were polyploidy, C-metaphase, stathmo-anaphase, ball metaphase, vagrants, tropokinesis, etc. The mitotic index was found to be decreasing with increase in concentration, whereas the abnormality percentage increased with an increase in the concentration of the plant extract. The in situ visualization of cell death by the Evan’s blue staining method gave a positive relation between the concentration of the extract and its apoptotic activity. Conclusion: As cytotoxicity and apoptosis are bioactivities related to anticancer potential, the study proves that the plant is of high therapeutic efficacy and requires more exploration toward its usefulness in drug discovery.